Deconstructing Disney - Byrne, Eleanor and McQuillan, Martin. (Pluto Press, 1999)
A close critical look at the new Disney canon - using deconstruction as a critical lever to engage with the films themselves, and the wider issues they raise.
https://katalog.adlr.link/Record/76-EBC3386046